2017
DOI: 10.1160/th16-07-0564
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo pathway regulates human megakaryocytic differentiation

Abstract: The Hippo pathway is involved in several biological processes in both flies and mammals. Recent studies have shown that the Hippo pathway regulates Drosophila's haematopoiesis; however, understanding of its role in mammalian haematopoiesis is still limited. In flies, deletion of the Hippo component gene, Warts, affects crystal cell differentiation. We explored the role of the Hippo pathway in human haematopoiesis focusing on megakaryopoiesis. To investigate the role of LATS1/2 (a mammalian homolog of Warts) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
(39 reference statements)
2
14
0
Order By: Relevance
“…We previously showed that reduction of the Hippo core kinase LATS1/2 inhibits platelet production [4]. In the present study, we further demonstrated that high expression of the Hippo pathway effector protein YAP induces MEG-01 cells to become more mature as shown by the increasing number of CD41 + cells, but these cells did not produce platelets.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…We previously showed that reduction of the Hippo core kinase LATS1/2 inhibits platelet production [4]. In the present study, we further demonstrated that high expression of the Hippo pathway effector protein YAP induces MEG-01 cells to become more mature as shown by the increasing number of CD41 + cells, but these cells did not produce platelets.…”
Section: Discussionsupporting
confidence: 69%
“…We previously demonstrated that Hippo pathway core kinase LATS1/2 plays an essential role in regulating megakaryocyte proliferation and differentiation [4]. In the present study, we further explored the role of the Hippo effector proteins YAP and TAZ on megakaryocyte differentiation and platelet production.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, the most important pathways, which could have a role in the pathophysiology of VTE, are discussed here; MAPK signaling pathways have been previously shown to be involved in the pathophysiology of thrombosis or platelet activity in a direct or indirect manner [31, 3842]. Similarly, the Hippo signaling pathway has been shown to play an important role in megakaryocyte differentiation and platelet production [41, 43]. HIF-1 pathway is known to promote endothelial permeability and activation, coagulopathy, and recruitment of inflammatory cells, and contribute to the initiation or development of venous thrombosis through its target genes [42].…”
Section: Discussionmentioning
confidence: 99%